The effect of aggregate’s shape properties on the packing structure of porous asphalt mixture (PAM) by utilising artificially-designed aggregates - Lim, Nicholas Rong Sheng (Nanyang Technological University, 2020)
The shape and surface texture of the aggregates have a significant impact on the performance and durability of porous asphalt mixture (PAM). Research has been done using limited variations in the shape properties presents in natural aggregates. This project aims to establish improved procedures in fabricating and testing of Marshall specimens. Different tests were carried out to evaluate the relationship between aggregate shape properties with the packing structure of PAM. A preliminary study was first carried out by using granite as the coarse aggregates for the fabrication of the PAM samples based on five gradations. This served to select a gradation with the most desirable performance by evaluating their performance test results. The performance tests are Marshall Stability and Flow Test, Water Permeability Test, Indirect Tensile Test and Dynamic Creep Test. After that, three experimental groups (i.e. EGA, EGB and EGC) with different shapes of artificially-designed aggregates (i.e. sphere (EGA), cube (EGB) and cylinder (EGC)) were studied and evaluated by incorporating them into the PAM specimens. Prior to the fabrication of specimens, square and cylinder metal rods were processed by cutting them into the required size based on their width and diameter respectively, with the ratio of one in width or diameter to its length. Bitumen of PG76 grade was used to bind the aggregates together which has better properties as compared to conventional PEN 60/70. Next, the experimental designs using aggregates of different shapes were evaluated through four laboratory tests which are the same performance tests as carried out in the preliminary study to evaluate the relationship between the aggregate shape properties with the packing structure of PAM. Based on the Marshall Stability and Flow Test and Indirect Tensile Test, it is observed that the roundness index of different shapes is inversely proportional to the Marshall stability and flow values, and the resilient modulus value. However, the roundness index of different shapes is directly proportional to the total permanent strain under the Dynamic Creep Test. Besides based on the water permeability test, it is noticed that PAM specimen made of coarse aggregates with a lower roundness index results in a shorter time taken to drain 2,000 cc of water. Shape with lower roundness index tends to produce less well compacted PAM specimens which results in higher voids content that enhances the drainage of water and it also increases the strength of the PAM specimens by enhancing the interlocking between the coarse aggregates. In contrast, the collected results show that the roundness index of the coarse aggregates does affect the strength of the road pavement.